Comparative in vitro evaluation of a biosimilar enoxaparin candidate and its reference product - Zuluaga, Andrés F.; Jiménez Toro, Ivone; Hincapie, Andrés (Vitae, 2025)
BACKGROUND: Enoxaparin, a low molecular weight heparin, has been widely used to prevent and treat thromboembolic disorders. Following the expiration of the patent of the reference product, biosimilar alternatives were developed, requiring thorough comparability assessments to ensure efficacy and safety. OBJECTIVE: To compare the in vitro pharmacodynamic and structural properties of Biotexin® and the reference product Clexane®. METHODS: The products were evaluated using anti-FXa chromogenic assays, clot-based tests (aPTT, TT), and whole-blood thromboelastometry (ROTEM). Structural analyses included molecular weight profiling and USP potency determination. RESULTS: Biotexin® showed anti-FXa activity comparable to that of Clexane®, with overlapping EC₅₀ confidence intervals. No statistically significant differences were observed in aPTT or TT assays (P = 0.499 and P = 0.538, respectively). ROTEM analysis confirmed a significant prolongation of clotting time (CT) and clot formation time (CFT) compared to the control (P = 0.0043 and P = 0.0064, respectively), with no differences between the two products. Molecular weight distribution and USP potency were also comparable. CONCLUSION: These findings confirm the in vitro biosimilarity between Biotexin® and the reference product, supporting their functional equivalence and justifying further pharmacokinetic and clinical studies to establish therapeutic interchangeability.